2018
DOI: 10.1111/and.13008
|View full text |Cite
|
Sign up to set email alerts
|

Endopeptidase inhibition attenuates the contraction induced by big endothelin‐1 of isolated human penile erectile tissue

Abstract: Peptides, such as C-type natriuretic peptide (CNP), vasoactive intestinal polypeptide (VIP) and endothelin 1 (ET-1), are involved in the control of penile erectile tissue (corpus cavernosum = CC). Inhibiting the degradation of CNP and VIP or conversion of Big ET-1 into ET-1 by endopeptidase enzymes should result in an enhancement of CC smooth muscle relaxation. Using the tissue bath technique, responses of isolated CC, challenged by noradrenaline (NA, 1 μm), to increasing concentrations of the endopeptidase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Penile erectile tissue (corpus cavernosum) was obtained from 5 individuals who had been subjected to gender reassignment surgery (male-to-female). Tissue bath experiments were conducted according to standard procedures, as has been described earlier [18,19]. A passive tension of 0.5 gr (5 mN) was applied to the strip preparations, followed by a resting period of 60 min.…”
Section: Tissue Bath Studies (Contraction-response Studies)mentioning
confidence: 99%
“…Penile erectile tissue (corpus cavernosum) was obtained from 5 individuals who had been subjected to gender reassignment surgery (male-to-female). Tissue bath experiments were conducted according to standard procedures, as has been described earlier [18,19]. A passive tension of 0.5 gr (5 mN) was applied to the strip preparations, followed by a resting period of 60 min.…”
Section: Tissue Bath Studies (Contraction-response Studies)mentioning
confidence: 99%
“…Comparatively, the mechanism of action of CNP is diverse and researchers in the last decade showed that CNP affects coronary blood flow regulation electrophysiology, vascular integrity, endothelial cell and smooth muscle proliferation, angiogenesis, leukocyte activation, and vascular tone ( Perez-Ternero et al ., 2019 ). In the male reproductive system, several studies showed that testicular function and fertility and regulation of erectile tissue can be regulated by CNP ( Hannema et al ., 2013 ; Shahin et al ., 2018 ; Ückert et al ., 2019 ).…”
Section: Introductionmentioning
confidence: 99%